Solid electrolyte, electrode material, lithium secondary battery, and method for producing solid electrolyte

By adding specific metal elements and fluorine to the solid electrolyte and performing annealing treatment, the crystal structure is optimized, and the problem of low ion conductivity of solid electrolytes in the prior art is solved, thereby achieving higher ion conductivity.

CN119744422APending Publication Date: 2025-04-01PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060395.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-21
Filing Date
2023-07-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the prior art, the ion conductivity of the solid electrolyte containing fluorine is low and needs to be improved.

Method used

Annealing is performed to improve ion conductivity by adding Li, Ti, M and F to the solid electrolyte, where M is a selected metal element such as Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr and Sn. The specific method includes annealing at a condition of 100°C or more and 10 hours or more, and determining the intensity ratio of the peak by X-ray diffraction to optimize the crystal structure.

Benefits of technology

Through this method, the ion conductivity of the solid electrolyte containing fluorine is significantly improved and its performance is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744422A_ABST
    Figure CN119744422A_ABST
Patent Text Reader

Abstract

A solid electrolyte (10) of the present disclosure contains Li, Ti, M, and F. M represents at least one element selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr, and Sn. In an X-ray diffraction pattern obtained by X-ray diffraction measurement using a CuK [alpha] ray, the ratio of the intensity of a peak present in the range of a diffraction angle 2 [theta] of 40-43 degrees (inclusive) to the intensity of a peak present in the range of a diffraction angle 2 [theta] of 19-23 degrees (inclusive) is 1.0-3.3 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a solid electrolyte, an electrode material, a lithium secondary battery, and a method for manufacturing the solid electrolyte. Background Art

[0002] Patent Document 1 discloses a solid electrolyte material containing Li, Ti, M, and F. M is at least one selected from the group consisting of Al and Y. Patent Document 1 describes that a solid electrolyte material containing fluorine has excellent oxidation resistance.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2021 / 186809 Summary of the invention

[0006] Problem that the invention aims to solve

[0007] Conventionally, there is a demand for improving the ion conductivity of a solid electrolyte containing fluorine.

[0008] Solutions for solving problems

[0009] The present disclosure provides a solid electrolyte comprising Li, Ti, M and F.

[0010] M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr and Sn,

[0011] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα rays, the ratio of the intensity of the peak existing in the diffraction angle 2θ range of 40° to 43° to the intensity of the peak existing in the diffraction angle 2θ range of 19° to 23° is 1.0 to 3.3.

[0012] Effects of the Invention

[0013] According to the present disclosure, the ion conductivity of a solid electrolyte containing fluorine can be improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a diagram showing a solid electrolyte in Embodiment 1.

[0015] Figure 2 It is a process diagram showing a method for producing a solid electrolyte.

[0016] Figure 3 This is a cross-sectional view showing a schematic structure of an electrode material in the second embodiment.

[0017] Figure 4 This is a cross-sectional view showing a schematic structure of a battery in the third embodiment.

[0018] Figure 5 This is a cross-sectional view of a lithium secondary battery in Embodiment 4.

[0019] Figure 6 This is a schematic diagram of a press molding die used for measuring ion conductivity.

[0020] Figure 7 It is a graph showing X-ray diffraction patterns of solid electrolytes of Examples and Comparative Examples.

[0021] Figure 8 This is a graph showing the relationship between the ratio I2 / I1 and the ion conductivity. DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.

[0023] (Implementation Method 1)

[0024] Figure 1 The solid electrolyte 10 in Embodiment 1 is shown. The solid electrolyte 10 contains Li, Ti, M and F. M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr and Sn. In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα rays, the ratio I2 / I1 of the intensity I2 of the peak existing in the range of diffraction angle 2θ of 40° to 43° to the intensity I1 of the peak existing in the range of diffraction angle 2θ of 19° to 23° is 1.0 to 3.3. The peak intensities I1 and I2 represent relative intensities.

[0025] The solid electrolyte 10 contains F and therefore has high oxidation resistance. The reason is that F has a high redox potential. On the other hand, F has a high electronegativity, so the combination of F and Li is relatively strong. Therefore, there is a tendency that the ion conductivity of the previous solid electrolyte containing Li and F is low. In contrast, the ratio of the intensity of the peaks in the X-ray diffraction pattern of the solid electrolyte 10 of the present embodiment, I2 / I1, is greater than 1.0 and less than 3.3. Thus, the solid electrolyte 10 shows a higher ion conductivity than the previous solid electrolyte containing Li, Ti, M and F. The peak intensity ratio I2 / I1 is increased by implementing a long annealing during the manufacturing process of the solid electrolyte 10.

[0026] It is speculated that the peak existing in the range of diffraction angle 2θ of more than 19° and less than 23° is a peak belonging to orthorhombic. It is speculated that the peak existing in the range of diffraction angle 2θ of more than 40° and less than 43° is a peak belonging to trigonal. It is speculated that by long-term annealing, the contribution of the crystal structure of the trigonal crystal increases relatively relative to the contribution of the crystal structure of the orthorhombic crystal, and as a result, the ion conductivity improves. When the crystal structure of the solid electrolyte 10 is close to the single-phase trigonal crystal, the ratio I2 / I1 is close to the upper limit of 3.3. The ratio of the intensity of the peak I2 / I1 can be more than 1.8 and less than 3.0.

[0027] A peak existing in the range of a diffraction angle 2θ of 19° to 23° refers to a peak with the maximum intensity existing in this range. A peak existing in the range of a diffraction angle 2θ of 40° to 43° refers to a peak with the maximum intensity existing in this range.

[0028] M may be at least one selected from the group consisting of Mg, Ca, Zr, and Al. These elements are suitable as elements for improving the ion conductivity of the solid electrolyte 10 .

[0029] M is typically Al. Al is inexpensive and particularly suitable as an element for improving the ion conductivity of the solid electrolyte 10 .

[0030] The solid electrolyte 10 preferably does not contain sulfur. A solid electrolyte that does not contain sulfur does not generate hydrogen sulfide even when exposed to the atmosphere, and therefore has excellent safety.

[0031] In order to improve ion conductivity, the solid electrolyte 10 may contain anions other than F. The anions other than F are at least one selected from the group consisting of Cl, Br, I, O, and Se.

[0032] The solid electrolyte 10 may be substantially composed of Li, Ti, M, and F. Here, "the solid electrolyte 10 is substantially composed of Li, Ti, M, and F" means that the molar ratio (i.e., molar fraction) of the total amount of Li, Ti, M, and F relative to the total amount of all elements constituting the solid electrolyte 10 is 90% or more. As an example, the molar ratio may be 95% or more. The solid electrolyte 10 may also be composed of only Li, Ti, M, and F.

[0033] However, the solid electrolyte 10 may also contain an element that is inevitably mixed in. Examples of such elements include hydrogen, oxygen, and nitrogen. Such elements are contained in the raw material powder of the solid electrolyte 10 or exist in the atmosphere used to manufacture and store the solid electrolyte 10.

[0034] In order to further improve the ion conductivity of the solid electrolyte 10 , the ratio of the amount of substance of Li to the total amount of substance of Ti and M may be 1.7 or more and 4.2 or less.

[0035] The solid electrolyte 10 has a composition represented by the following formula (1), for example. The formula (1) satisfies 0<x<1 and 0<b≤2. When the solid electrolyte 10 has a composition represented by the following formula (1), the solid electrolyte 10 exhibits good ion conductivity.

[0036] Li 6-(4-x)b (Ti 1-x M x ) b F6……Formula (1)

[0037] In order to improve the ionic conductivity of the solid electrolyte 10, the formula (1) may satisfy 0.1≤x≤0.9.

[0038] In order to improve the ionic conductivity of the solid electrolyte 10, the formula (1) may satisfy 0.8≤b≤1.2.

[0039] The appearance of peaks in the X-ray diffraction pattern indicates that solid electrolyte 10 has a crystalline phase. However, solid electrolyte 10 may include an amorphous phase.

[0040] The shape of the solid electrolyte 10 is not particularly limited. The solid electrolyte 10 may have a particle shape. Examples of the particle shape include a needle shape, a spherical shape, an ellipsoidal spherical shape, and the like. The solid electrolyte 10 may have a pellet, a plate, or a thin film shape.

[0041] When the solid electrolyte 10 is granular, the particles of the solid electrolyte 10 may have a median particle size of 0.01 μm or more and 100 μm or less. As a result, the solid electrolyte 10 shows a higher ion conductivity. Furthermore, when the solid electrolyte 10 is mixed with other materials such as an active material, the dispersion state of the solid electrolyte 10 and the other materials becomes good. "Median particle size" refers to the particle size at which the cumulative volume in the volume-based particle size distribution becomes 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction particle size distribution measuring device.

[0042] Next, a method for producing the solid electrolyte 10 will be described. Figure 2 It is a process diagram showing a method for producing a solid electrolyte.

[0043] In step S1, a solid electrolyte is synthesized. First, raw material powders are mixed to obtain a solid electrolyte having a target composition. The raw material powders are, for example, fluorides of various elements. For example, the target composition is Li 2.7 Ti 0.3 Al 0.7In the case of F6, LiF, TiF4 and AlF3 are mixed in a molar ratio of 2.7:0.3:0.7. Then, the raw material powders are reacted with each other using a mixing device such as a planetary ball mill. That is, the raw material powders are reacted with each other using a mechanochemical grinding method. Thus, a solid electrolyte having a target composition can be obtained.

[0044] Next, in step S2, the obtained solid electrolyte is annealed. Annealing is performed at a temperature of 100° C. or higher and for 10 hours or longer. Thus, the solid electrolyte 10 of the present embodiment can be obtained. By performing annealing for a long time at a suitable temperature, the peak intensity ratio I2 / I1 increases. As a result, the ion conductivity of the solid electrolyte 10 is improved.

[0045] The upper limit of the annealing temperature is not particularly limited, for example, 270°C. The upper limit of the annealing time is not particularly limited, for example, 1000 hours. The annealing conditions are preferably above 120°C and below 250°C, and above 10 hours and below 200 hours. The atmosphere during annealing can be an air atmosphere or an inert atmosphere. Examples of inert atmospheres include nitrogen atmospheres, rare gas atmospheres, and the like.

[0046] Before or after annealing, a step of pulverizing the solid electrolyte 10 may be performed. In this step, the solid electrolyte 10 is pulverized to have a median particle size of, for example, nanometers.

[0047] (Implementation Method 2)

[0048] Figure 3 4 is a cross-sectional view of the electrode material 20 in Embodiment 2. The electrode material 20 includes an active material 30 and a covering layer 40. The covering layer 40 covers at least a portion of the surface of the particles of the active material 30. The active material 30 may be a secondary particle formed by agglomerating a plurality of primary particles. The covering layer 40 may cover at least a portion of the surface of the secondary particles of the active material 30. The covering layer 40 includes the solid electrolyte 10 of Embodiment 1. When the active material 30 is covered by the solid electrolyte 10, direct contact between other materials such as an electrolyte and the active material 30 can be blocked. As a result, decomposition of other materials such as an electrolyte can be suppressed.

[0049] The covering layer 40 may cover only a portion of the surface of the particles of the active material 30. In this case, the particles of the active material 30 are in direct contact with each other via the portion not covered by the covering layer 40, thereby ensuring the electron conductivity between the particles of the active material 30. However, the covering layer 40 may uniformly cover the surface of the particles of the active material 30.

[0050] The covering layer 40 may contain the solid electrolyte 10 as a main component, or may contain only the solid electrolyte 10. "Main component" refers to the component contained in the largest amount by mass ratio. "Containing only the solid electrolyte 10" means that no material other than the solid electrolyte 10 is intentionally added except for unavoidable impurities.

[0051] The active material 30 is, for example, a positive electrode active material. When the electrode material 20 is used in the positive electrode of the nonaqueous electrolyte secondary battery, decomposition of the electrolyte in the positive electrode can be suppressed. Therefore, a higher-output active material can be used for the positive electrode.

[0052] When the electrode material 20 is used as the positive electrode of the solid battery, a second solid electrolyte having a different composition from the solid electrolyte 10 is mixed in the positive electrode. In this case, direct contact between the active material 30 and the second solid electrolyte is blocked, so decomposition of the second solid electrolyte can be suppressed. Examples of the second solid electrolyte include halide solid electrolytes, sulfide solid electrolytes, polymer solid electrolytes, complex hydride solid electrolytes, and the like. Examples of sulfide solid electrolytes include Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 Etc. As polymer solid electrolytes, compounds of polymer compounds having an ethylene oxide structure and lithium salts can be listed. As lithium salts, for example, at least one selected from the group consisting of LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) and LiC(SO2CF3)3 can be used. As complex hydride solid electrolytes, LiBH4-LiI, LiBH4-P2S5, etc. can be listed. As halide solid electrolytes, Li3YX6, Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, etc. can be listed. "X" is a halogen element. "(Al,Ga,In)" refers to at least one selected from the group consisting of Al, Ga and In. One or a combination of two or more selected from these solid electrolytes can be used as the second solid electrolyte.

[0053] Active material 30 includes a material having the property of absorbing and releasing metal ions such as lithium ions.

[0054] When the active material 30 is a positive electrode active material, a lithium-containing transition metal oxide, a lithium-containing transition metal phosphate, a transition metal fluoride, a polyanion material, a fluorinated polyanion material, a transition metal sulfide, a transition metal oxysulfide, a transition metal oxynitride, etc. can be used as the active material 30. In particular, when a lithium-containing transition metal oxide or a lithium-containing transition metal phosphate is used as the active material 30, the manufacturing cost of the battery can be reduced and the average discharge voltage can be increased. As lithium-containing transition metal oxides, lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium nickel manganese oxide, etc. can be listed. As lithium-containing transition metal phosphates, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium nickel phosphate, etc. can be listed.

[0055] The active material 30 may be a negative electrode active material. Examples of the negative electrode active material include lithium titanate, graphite, silicon, silicon compounds, and NiBi alloys.

[0056] The active material 30 has a particle shape, for example. The shape of the particles of the active material 30 is not particularly limited. The shape of the particles of the active material 30 may be spherical, ellipsoidal, scaly, or fibrous.

[0057] The electrode material 20 can be produced by the following method.

[0058] The powder of the active material 30 and the powder of the solid electrolyte 10 are mixed in an appropriate ratio to obtain a mixture. The mixture is subjected to a grinding process to impart mechanical energy to the mixture. A mixing device such as a ball mill can be used for the grinding process. In order to suppress oxidation of the material, the grinding process can also be performed in a dry atmosphere and an inert atmosphere.

[0059] The electrode material 20 can be manufactured by a dry particle composite method. The treatment based on the dry particle composite method includes applying at least one mechanical energy selected from the group consisting of impact, compression and shear to the active material 30 and the solid electrolyte 10. The active material 30 and the solid electrolyte 10 are mixed in an appropriate ratio.

[0060] The device used in the manufacture of the electrode material 20 is not particularly limited, and can be a device that can impart mechanical energy of impact, compression and shear to the mixture of the active material 30 and the solid electrolyte 10. As a device that can impart mechanical energy, a ball mill, "MECHANO FUSION" (manufactured by Hosokawa Micron Corporation), "NOBILTA" (manufactured by Hosokawa Micron Corporation), "BALANCE GRAN" (manufactured by Freund-Turbo Corporation) and other processing devices (particle composite devices) can be listed. The electrode material 20 can also be manufactured by a liquid phase method such as a sol-gel method.

[0061] Reference Figure 2 The annealing step (step S2 ) described above can be performed in a state where the unannealed solid electrolyte is attached to the particle surface of the active material 30 .

[0062] A second covering layer may be present between the active material 30 and the covering layer 40. The second covering layer may be formed of an oxide solid electrolyte such as LISICON or lithium niobate.

[0063] It is not essential to use the solid electrolyte 10 as a covering material for the active material 30. The solid electrolyte 10 can be used as an electrolyte layer of a solid battery.

[0064] (Implementation method 3)

[0065] Figure 4 1 is a cross-sectional view of a lithium secondary battery 100 in Embodiment 3. The lithium secondary battery 100 includes a positive electrode 53, a negative electrode 56, an electrolyte layer 57, a housing 58, and a non-aqueous electrolyte 59. The positive electrode 53 includes a positive electrode collector 51 and a positive electrode active material layer 52. The positive electrode active material layer 52 is disposed on the positive electrode collector 51. The negative electrode 56 includes a negative electrode collector 54 and a negative electrode active material layer 55. The negative electrode active material layer 55 is disposed on the negative electrode collector 54. An electrolyte layer 57 is disposed between the positive electrode 53 and the negative electrode 56. The electrolyte layer 57 is a separator. The positive electrode 53, the negative electrode 56, the electrolyte layer 57, and the non-aqueous electrolyte 59 are housed in a housing 58.

[0066] The positive electrode 53 or the negative electrode 56 includes the electrode material 20 of Embodiment 2. Specifically, the positive electrode active material layer 52 or the negative electrode active material layer 55 includes the electrode material 20 of Embodiment 2. Thus, in the positive electrode 53 or the negative electrode 56, decomposition of other materials such as the nonaqueous electrolyte 59 is suppressed. As a result, performance such as the cycle life of the lithium secondary battery 100 is improved.

[0067] The electrode material 20 is typically contained in the positive electrode 53. Thus, decomposition of the non-aqueous electrolyte 59 in the positive electrode 53 can be suppressed.

[0068] The positive electrode current collector 51 is a foil made of a metal material such as aluminum, stainless steel, titanium, or an alloy thereof. The negative electrode current collector 54 is a foil made of a metal material such as stainless steel, nickel, copper, or an alloy thereof.

[0069] The positive electrode active material layer 52 and the negative electrode active material layer 54 may contain a conductive additive, an ion conductor, a binder, and the like.

[0070] The non-aqueous electrolyte 59 is impregnated in the positive electrode 53, the negative electrode 56, and the electrolyte layer 57. The non-aqueous electrolyte 59 may also fill the inner space of the outer case 58.

[0071] The nonaqueous electrolyte 59 contains a nonaqueous solvent and a lithium salt.

[0072] As the non-aqueous solvent, cyclic carbonate, chain carbonate, ester, cyclic ether, chain ether, nitrile, amide, etc. can be used. One kind selected from these solvents can be used alone, or two or more kinds can be used in combination.

[0073] As lithium salts, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiN(SO2C2F5)2), LiAsF6, LiCF3SO3, lithium difluorooxalatoborate, etc. can be used. One selected from these electrolyte salts can be used, or two or more can be used in combination.

[0074] The electrolyte layer 57 has lithium ion conductivity. The material of the electrolyte layer 57 is not particularly limited as long as it allows lithium ions to pass through. The material of the electrolyte layer 57 can be at least one selected from the group consisting of a solid electrolyte, a gel electrolyte, an ion exchange resin membrane such as a lithium cation exchange resin, a semipermeable membrane, and a porous membrane. When the electrolyte layer 57 is made of these materials, the safety of the lithium secondary battery 100 can be fully ensured. As solid electrolytes, sulfide solid electrolytes such as Li2S-P2S5, Li7La3Zr2O 12 (LLZ) and other oxide solid electrolytes. As the gel electrolyte, a gel electrolyte containing a fluororesin such as PVdF can be listed. As the ion exchange resin membrane, a cation exchange membrane, an anion exchange membrane, etc. can be listed. As the porous membrane, a porous membrane made of polyolefin resin, a porous membrane composed of glass paper obtained by weaving glass fibers into non-woven fabric, etc. can be listed. The electrolyte layer 57 has a thickness of, for example, 0.001 μm or more and 500 μm or less.

[0075] As the solid electrolyte of the electrolyte layer 57 , the solid electrolyte 10 of the first embodiment can be used.

[0076] The shape of the lithium secondary battery 100 is not particularly limited. The lithium secondary battery 100 may be in various shapes such as a coin shape, a cylinder shape, a square shape, a sheet shape, a button shape, a flat shape, and a stacked shape.

[0077] (Implementation 4)

[0078] Figure 5: is a cross-sectional view of a lithium secondary battery 200 in Embodiment 4. The lithium secondary battery 200 includes a positive electrode 63, a covering layer 68, an electrolyte layer 67, and a negative electrode 66 in this order. The electrolyte layer 67 is arranged between the positive electrode 63 and the negative electrode 66. The positive electrode 63 includes a positive electrode collector 61 and a positive electrode active material layer 62. The negative electrode 66 includes a negative electrode collector 64 and a negative electrode active material layer 65. The covering layer 68 is a layer including the solid electrolyte 10 of Embodiment 1, and is arranged between the positive electrode active material layer 62 and the electrolyte layer 67 to cover the surface of the positive electrode active material layer 62. In detail, the covering layer 68 is arranged on the surface of the positive electrode active material layer 62, and is in contact with both the positive electrode active material layer 62 and the electrolyte layer 67.

[0079] The cover layer 68 may contain a binder. As the binder, the same material as that used for the positive electrode active material layer 62 and the negative electrode active material layer 65 can be used. The cover layer 68 has a thickness of, for example, 0.001 μm or more and 100 μm or less.

[0080] The electrolyte layer 67 may be a layer containing a second solid electrolyte. When the electrolyte layer 67 contains the second solid electrolyte, the total thickness of the cover layer 68 and the thickness of the electrolyte layer 67 is, for example, 0.002 μm or more and 500 μm or less. According to this embodiment, the effect of suppressing the decomposition of the second solid electrolyte can be obtained on the basis of improving the ion conductivity.

[0081] The position of the cover layer 68 is not limited to Figure 5 The covering layer 68 may be provided between the electrolyte layer 67 and the negative electrode active material layer 65. The covering layer 68 may be disposed on the surface of the negative electrode active material layer 65. Alternatively, the covering layer 68 may be disposed only between the electrolyte layer 67 and the negative electrode active material layer 65. The covering layer 68 may be disposed on the surface of at least one of the positive electrode active material layer 62 and the negative electrode active material layer 65.

[0082] The constituent materials of the lithium secondary battery 200 are as described in Embodiment 3. The lithium secondary battery 200 may be a solid battery that does not use a liquid electrolyte, or may be a secondary battery that uses a non-aqueous electrolyte as described in Embodiment 3.

[0083] (Other embodiments)

[0084] (appendix)

[0085] Based on the description of the above embodiments, the following technology is disclosed.

[0086] (Technology 1)

[0087] A solid electrolyte comprising Li, Ti, M and F,

[0088] M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr and Sn,

[0089] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα rays, the ratio of the intensity of the peak existing in the diffraction angle 2θ range of 40° to 43° to the intensity of the peak existing in the diffraction angle 2θ range of 19° to 23° is 1.0 to 3.3.

[0090] With this configuration, the ion conductivity of the solid electrolyte containing fluorine can be improved.

[0091] (Technique 2)

[0092] The solid electrolyte according to technology 1, wherein M is at least one selected from the group consisting of Mg, Ca, Zr, and Al. These elements are suitable as elements for improving the ion conductivity of the solid electrolyte.

[0093] (Technique 3)

[0094] The solid electrolyte according to technology 1, wherein M is Al. Al is inexpensive and particularly suitable as an element for improving the ion conductivity of the solid electrolyte.

[0095] (Technique 4)

[0096] The solid electrolyte according to the technique 1, wherein the solid electrolyte has a composition represented by the following formula (1). Formula (1) satisfies 0<x<1 and 0<b≤2. With this composition, the solid electrolyte exhibits good ion conductivity.

[0097] Li 6-(4-x)b (Ti 1-x M x ) b F6……Formula (1)

[0098] (Technique 5)

[0099] An electrode material comprising:

[0100] Active substances, and

[0101] a coating layer covering at least a portion of the surface of the particles of the active substance,

[0102] The aforementioned covering layer contains the solid electrolyte described in any one of Techniques 1 to 4.

[0103] This configuration prevents direct contact between the active material and other materials such as the electrolyte, thereby suppressing decomposition of other materials such as the electrolyte.

[0104] (Technique 6)

[0105] A lithium secondary battery comprising:

[0106] positive electrode,

[0107] Negative electrode, and

[0108] an electrolyte layer disposed between the positive electrode and the negative electrode,

[0109] The positive electrode or the negative electrode comprises the electrode material described in Technology 5.

[0110] With this configuration, performance such as the cycle life of the lithium secondary battery is improved.

[0111] (Technique 7)

[0112] A method for manufacturing a solid electrolyte, comprising the following operations:

[0113] synthesizing a solid electrolyte comprising Li, Ti, M and F; and

[0114] annealing the solid electrolyte at 100° C. or higher for 10 hours or longer,

[0115] M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr, and Sn.

[0116] With this configuration, the ion conductivity of the solid electrolyte containing fluorine can be improved.

[0117] Example

[0118] (Comparative Example 1)

[0119] In an argon atmosphere with a dew point below -60°C, LiF, TiF4 and AlF3 as raw material powders were weighed in a molar ratio of LiF:TiF4:AlF3=2.7:0.3:0.7. These were crushed in a mortar and mixed to obtain a mixture. Then, the mixture was ground using φ5 mm spherical zirconium oxide and a planetary ball mill (manufactured by Fritsch GmbH, P-7 model) for 12 hours at 500 rpm. Thus, Li 2.7 Ti 0.3 Al 0.7 A powdered solid electrolyte composed of F6.

[0120] (Example 1)

[0121] The solid electrolyte of Comparative Example 1 was placed in a sealed container and annealed under the conditions of 125° C. (ambient temperature) in an air atmosphere for 40 hours. Thus, the solid electrolyte of Example 1 was obtained.

[0122] (Example 2)

[0123] The solid electrolyte of Comparative Example 1 was placed in a sealed container and annealed under the conditions of 150° C. (ambient temperature) in an air atmosphere for 90 hours. Thus, a solid electrolyte of Example 2 was obtained.

[0124] [Measurement of ion conductivity]

[0125] Figure 6 Schematic diagram showing a press mold 300 used to measure the ion conductivity of a solid electrolyte. The press mold 300 includes an upper punch 301, a die frame 302, and a lower punch 303. The upper punch 301 and the lower punch 303 are made of stainless steel. The die frame 302 is made of polycarbonate.

[0126] The solid electrolyte powder 101 was filled in the press-forming die 300 in a dry atmosphere having a dew point of −60° C. or less. The upper punch 301 and the lower punch 303 were used to apply a pressure of 400 MPa to the solid electrolyte powder 101 .

[0127] Under pressure, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to the working electrode and the potential measurement terminal. The lower punch 303 was connected to the counter electrode and the reference electrode. The impedance of the solid electrolyte was measured by electrochemical impedance spectroscopy at 25°C and -40°C.

[0128] In the Cole-Cole diagram obtained by impedance measurement, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest is regarded as the resistance value of the solid electrolyte to ion conduction. Using this resistance value, the ion conductivity is calculated based on the following formula (2). The results are shown in Table 1.

[0129] σ=(R SE ×S / t) -1 ……(2)

[0130] In formula (2), σ represents the ion conductivity. S represents the contact area between the solid electrolyte and the upper punch 301. Figure 6 R is equal to the cross-sectional area of ​​the hollow portion of the mold frame 302. SE represents the resistance value of the solid electrolyte in the impedance measurement. t represents the thickness of the solid electrolyte. Figure 6Here, t represents the thickness of the layer of the solid electrolyte powder 101 .

[0131] [X-ray diffraction measurement]

[0132] Powder X-ray diffraction measurement was performed on the solid electrolytes of Comparative Example 1, Example 1, and Example 2. A powder X-ray diffraction apparatus (MiniFlex600 manufactured by Rigaku Corporation) was used for the X-ray diffraction measurement.

[0133] Using Cu-Kα radiation (wavelength and ) was used as the X-ray source, and the measurement was performed using the θ-2θ method. The measurement angle interval was 0.01°. The divergence angle of the divergence slit was 0.25°. The slit width of the length-limiting slit was 5 mm.

[0134] Figure 7 The X-ray diffraction pattern obtained by X-ray diffraction measurement is shown. The ratio I2 / I1 of the intensity I2 of the peak existing in the range of diffraction angle 2θ of 40° or more and 43° or less relative to the intensity I1 of the peak existing in the range of diffraction angle 2θ of 19° or more and 23° or less is calculated. The fitting of each peak uses the Gauss-Lorentz composite function. The results are shown in Table 1.

[0135] [Table 1]

[0136]

[0137] The ionic conductivity of the solid electrolyte of Example 2 at 25°C is about 1.5 times the ionic conductivity of the solid electrolyte of Comparative Example 1 at 25°C. Furthermore, the level of ionic conductivity of the solid electrolyte of Example 2 at -40°C is one order of magnitude greater than the level of ionic conductivity of the solid electrolyte of Comparative Example 1 at -40°C.

[0138] Figure 8 : is a graph showing the relationship between the ratio I2 / I1 and the ion conductivity at -40°C. In the solid electrolyte of Comparative Example 1, the ratio I2 / I1 is 0.45. In the solid electrolyte of Example 1, the ratio I2 / I1 is 1.99. In the solid electrolyte of Example 2, the ratio I2 / I1 is 2.66. From this result, it can be seen that the ratio I2 / I1 increases with the increase of annealing time.

[0139] Even if the metal M contained in the solid electrolyte is a metal other than Al, it is presumed that, for example, when the ion radius of the metal M is close to the ion radius of Al, the solid electrolyte has the same tendency as the solid electrolytes of Examples 1 and 2. Examples of such metal M include Ca, Mg, and Zr.

[0140] Industrial Applicability

[0141] The technology of the present disclosure is useful in lithium secondary batteries.

Claims

1. A solid electrolyte comprising Li, Ti, M and F, M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr and Sn, In the X-ray diffraction pattern obtained by X-ray diffraction measurement using CuKα rays, the ratio of the intensity of the peak existing in the diffraction angle 2θ range of 40° to 43° to the intensity of the peak existing in the diffraction angle 2θ range of 19° to 23° is 1.0 to 3.

3.

2. The solid electrolyte according to claim 1, wherein M is at least one selected from the group consisting of Mg, Ca, Zr and Al.

3. The solid electrolyte according to claim 1, wherein M is Al.

4. The solid electrolyte according to claim 1, wherein The solid electrolyte has a composition represented by the following formula (1): Li 6-(4-x)b (Ti 1-x M x ) b F6……Formula (1) Formula (1) satisfies 0<x<1 and 0<b≤2.

5. An electrode material comprising: Active substances, and a covering layer covering at least a portion of the surface of the particles of the active substance, The covering layer comprises the solid electrolyte according to claim 1 .

6. A lithium secondary battery comprising: positive electrode, Negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode, The positive electrode or the negative electrode comprises the electrode material according to claim 5.

7. A method for manufacturing a solid electrolyte, comprising the following operations: synthesizing a solid electrolyte comprising Li, Ti, M and F; and annealing the solid electrolyte at a temperature of 100° C. or higher for 10 hours or longer, M is at least one selected from the group consisting of Mg, Ca, Sr, Ba, Sc, Y, Al, Ga, In, Zr, and Sn.

Citation Information

Patent Citations

  • Solid electrolyte material and cell using same

    WO2021186809A1